EDGE COMPUTING ON DIGITAL DEVICES - Santosh Behera , Srikanta Sahoo (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper will examine basic aspects of the edge computing architecture and its connection with industrial applications as part of a concrete analysis undertaken to provide evidence supporting the use of edge technologies in demanding Industry 4.0 environments, including smart factories and smart farming. It also presents findings on accuracy improvements that compare traditional machine learning techniques for many important tasks, such as classification of images and speech recognition, how edge applications implement Artificial Intelligence (AI) to assist users in tasks such as virtual reality, face recognition, and smart personal assistants. Research such as this lead the current analysis to agree that when paired with edge apps, AI has tremendous potential and could unlock the efficiency of existing "not-smart" applications. The aim of this paper is to present some important findings in this field, compare key architectural aspects and provide a broad view of how edge solutions could be designed. After explaining how edge computing operates and presenting an overview of how it can be applied to industrial plants, the final section of this paper discusses ways of promoting the use of artificial intelligence on edge applications, creating a new source of "smart technologies" for existing environments.